Remineralization and inactivation of carious lesions treated with silver fluoride in Brazilian children with special healthcare needs - Potgieter, Nicoline; Pereira, Viviane; Elias, Roberto; Charone, Senda; Groisman, Sonia (Frontiers in Oral Health, 2024)
Background: Providing conventional, restorative dental care to children with special health care needs (CSHCN) often requires sedation of general anaesthesia. The saliva consistency, diet and oral hygiene practice is different for CSHCN, and limited evidence is available on the efficacy of SF for management of carious lesions for this vulnerable population. Methods: Parents of CSHCN, were educated about Silver Fluoride as a treatment option for caries. From 100 participants, 550 carious lesions were identified and scored according to the Nyvad Caries criteria. 100 lesions with Nyvad scores 1, 2 and 3 were treated with a single application of Silver Fluoride and observed postoperatively at 1, 3 and 6 weeks. Result: The results indicate statistically significant (p<0.05) differences in lesion remineralization over 6 weeks follow up period. At 6 weeks follow-up more than 85% of all lesions were remineralized across all children, regardless of condition or original Nyvad score 1, 2 or 3. Conclusion: A single application of Silver Fluoride has demonstrated effectiveness in remineralization and inactivation of carious lesions over 6 weeks, among Brazilian CSHCN. Silver Fluoride should be considered as an option for management of carious lesions among CSHCN. Further studies are recommended including larger sample sizes, longer follow-up times, a second application of SF and different special needs conditions.